In-vitro accuracy of the virtual patient model with maxillomandibular relationship at centric occlusion using 3D-printed customized transfer key - Anh Ho-Quynh Nguyen; Nam Cong-Nhat Huynh; Oanh Ngoc-Hoang Nguyen; Nhat Dinh-Minh Nguyen; Hai Hoang Phan; Jong-Eun Kim; Gan Jin; Khanh Hung Nguyen; Hung Trong Hoang (BDJ Open)
Abstract Objective This study aimed to create a 3D-printed customized transfer key and evaluate the accuracy of the virtual patient model with maxillomandibular relationship at centric occlusion using the transfer key. Methods A 3D-printed transfer key was designed, combining facial and intraoral (IOS) scans. The design included components that recorded the 3D upper and lower arch at centric occlusion. The virtual patient model image was generated in-vitro using a phantom head with soft tissue simulation. Accuracy was assessed by superimposing the 3D scans with reference CBCT images and analyzing trueness and precision using root mean square (RMS) deviations. Results The transfer key included an intra-oral part that acts as an anterior deprogrammer to record the relationship of two dental arches at centric occlusion (CO) and an extra-oral with a rotatable cross-shaped design with two arms for locating the facial midline and the two pupils connecting line. Superimposition demonstrated high trueness (RMS: 0.51 mm for the arch regions, 0.69 mm for the whole head region, 0.85 mm in the face region) and precision (RMS: 0.41 mm for the arch regions, 0.52 mm for the entire head, 0.63 mm in the face region) significantly (p < 0.05). Minimal deviations were observed in critical areas, including the tooth and lip position, indicating that the virtual patient model was closely aligned with the CBCT reference. The dental arches achieved the highest accuracy, while slight deviations were noted in the facial regions. Conclusions The 3D-printed customized transfer key effectively enhanced the virtual patient model’s accuracy, surpassing traditional trueness and precision methods. This novel approach offers a streamlined, patient-friendly solution for digital dental workflows.